Incorporating I-131 into a PAMAM (G5.0) dendrimerconjugate: design of a theranostic nanosensor for medullary thyroid carcinoma - He, R.; Wang, H.; Su, Y.; Chen, C.; Xie, L.; Chen, L.; Yu, J.; Toledo, Y.; Abayaweera, G. S.; Zhu, G.; Bossmann, Stefan H. (My University, 2017)
We report the synthesis and purification of a targeting probe for Medullary Thyroid Carcinoma (MTC) by incorporating I-131 into PAMAM (G5.0) dendrimers. Both the I-131 labeled control dendrimer (I-131-PAMAM (G5.0) without attached targeting peptide) and the MTC-targeting dendrimer (I-131-PAMAM (G5.0) attached to VTP (vascular targeting peptide)) were labeled with the radioisotope I-131 by applying the iodogen method. The resulting G5.0 dendrimers were purified by means of ultracentrifugation. The labelling efficiencies and radiochemical purities vs. time were determined by paper chromatography. The radiolabeling efficiencies of I-131-PAMAM (G5.0) and I-131-PAMAM (G5.0) were 93 +/- 1% and 85 +/- 2%, respectively. I-131-PAMAM (G5.0) did exhibit small, but significant changes in radiochemical purity as a function of time after labelling. The highest observed highest purity was 82 +/- 2%. I-131-PAMAM (G5.0)VTP did display larger changes in radiochemical purity as a function of time after labelling, maximally 80 +/- 2%. The stability of the two probes and their binding behavior to the human medullary thyroid cancer cell line (TT) were observed in vitro. Compared to the negative control group (consisting of (NaI)-I-131), the TT cell binding rate of 131I-PAMAM (G5.0)-VTP was significantly increased at 48 h and 72 h (P < 0.01). The TT cell binding rate of I-131-PAMAM (G5.0)-VTP at 48 h and 72 h was not significantly different when compared to the positive control group (I-131-PAMAM (G5.0) group) (P > 0.05). These findings have been confirmed by performing MTT assays. These results confirm earlier findings, which demonstrated fast uptake of PAMAM (G5.0) by various cell types.
Citation: He, R., Wang, H., Su, Y., Chen, C., Xie, L., Chen, L., . . . Bossmann, S. H. (2017). Incorporating I-131 into a PAMAM (G5.0) dendrimerconjugate: design of a theranostic nanosensor for medullary thyroid carcinoma. Rsc Advances, 7(26), 16181-16188. doi:10.1039/c7ra00604g
Keywords: Oral-Drug Delivery; Starburst Dendrimers; Nubase Evaluation; Decay; Properties; Cancer